IMPLEMENTASI MODEL PEMBELAJARAN SOFT-SKILL DALAM MEMBENTUK MORALITAS SISWA DI SDN 1 MONTONG BAAN SELATAN - Abdul Manap (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to describe the implementation of a soft-skill learning model in shaping students’ morality at SDN 1 Montong Baan Selatan. The approach used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results show that the application of a soft-skill learning model involving aspects of communication, cooperation, responsibility, and empathy is able to enhance students’ moral awareness in daily life. Teachers play an active role as facilitators in integrating moral values into the learning process, both through thematic approaches and extracurricular activities. The obstacles encountered include students’ limited initial understanding of soft-skill concepts and time constraints in implementation. This study recommends strengthening teacher training and developing a more adaptive curriculum oriented toward soft-skill development in order to support the sustainable formation of students’ morality.